Health Promotion with Counseling on Fulfilling Balanced Nutritional Needs for Community Groups in Pandemic Covid 19 Outbreak - Nurhidayat Nurhidayat; Suhanda Suhanda; Doni Setiawan; Heri Ariyanto; Henri Setiawan (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Covid-19 pandemic could increase forms of malnutrition such as overweight and micronutrient deficiencies. Fruits and vegetables are the best sources of vitamins and minerals. The content of vitamins and minerals can act as antioxidant compounds. The method used in this service activity consists of the planning stage, the implementation of the activity, and ends with an evaluation as a measure of the level of success. Health education is carried out by means of lectures and question and answer sessions, educational media using leaflets and PowerPoint Presentations. Results: the evaluation shows that the activities have been carried out well in accordance with the results indicators and criteria on the Evaluation Sheet instrument. The sheet is based on five dimensions, namely Punctuality and Duration, Participation, Knowledge, Job Description and Problem Solving. The content of the evaluation is carried out by two independent observers.